The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/jbt.21500
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐Converting Enzyme Inhibition and Angiotensin AT1 Receptor Blockade Downregulate Angiotensin‐Converting Enzyme Expression and Attenuate Renal Injury in Streptozotocin‐Induced Diabetic Rats

Abstract: Angiotensin-converting enzyme (ACE) is upregulated in the diabetic kidney and contributes to renal injury. This study investigates the possible beneficial effects of the ACE inhibitor (ACEI), enalapril and the AT1 receptor blocker (ARB), valsartan, on renal ACE expression, renal structure, and function in streptozotocin (STZ)-induced diabetic rats. Male Wistar rats were allocated into four groups: control, STZ-diabetic rats, and STZ-diabetic rats treated with either enalapril (10 mg/kg/day) or valsartan (50 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Thus, the inhibitory action of DBD on α-SMA suggests its potential anti-fibrotic effect that may protect against diabetic nephropathy. HYP is a specific amino acid of collagen; and widely used as a marker for collagen production [36]. We also detected reduced HYP secretion in DBD-treated GMCs, which further supports the anti-fibrotic effect of DBD in diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, the inhibitory action of DBD on α-SMA suggests its potential anti-fibrotic effect that may protect against diabetic nephropathy. HYP is a specific amino acid of collagen; and widely used as a marker for collagen production [36]. We also detected reduced HYP secretion in DBD-treated GMCs, which further supports the anti-fibrotic effect of DBD in diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 83%
“…ACE inhibitors had been shown to attenuate the progression of cardiac and renal impairments related to diabetes by different mechanisms: suppression of ACE upregulation, improvement of endothelial function, and protective antioxidant action (O'Driscoll et al , ; de Cavanagh et al , ; Motawi et al , ). Our results showed that in the presence of enalapril salivary TAC, as an indicator of overall antioxidant protection, in hypertensive patients with and without DM type 2 was similar to that in healthy subjects while in the presence of metoprolol was reduced in hypertensive patients with and without DM type 2.…”
Section: Discussionmentioning
confidence: 99%
“…Renal pathophysiology is elicited by activation of angiotensin II type 1 (AT1) receptors at all stages of renovascular disease. It has been reported that hyperglycaemia directly activate mesangial and proximal tubular cells renin angiotensin system which is responsible for the production of angiotensin II that activate the AT1 receptor . Activation of AT1 receptor results in haemodynamic and trophic effects leading to glomerular hypertension, hyperfiltration and increased production of TGF‐β1 that contribute to the pathogenesis of renal damage .…”
Section: Introductionmentioning
confidence: 99%
“…Activation of AT1 receptor results in haemodynamic and trophic effects leading to glomerular hypertension, hyperfiltration and increased production of TGF‐β1 that contribute to the pathogenesis of renal damage . For many years, AT1‐receptor blockers have been widely used for slowing down or preventing renal damage in diabetes . It is reported that the renoprotective effect of valsartan as AT1 antagonist is associated with improved renal function, reduced albuminuria, decline in glomerular filtration rate and glomerulosclerotic index in addition to decreased expression of TGF‐β1 .…”
Section: Introductionmentioning
confidence: 99%